Women defining water, energy, food, and ecosystems leadership in Nepal - Koirala, Sanju (International Water Management Institute, 2024)
The Water–Energy–Food–Ecosystems (WEFE) Nexus Leadership Program in Nepal aims to not only strengthen leadership and negotiation skills, but to create champions equipped with the technical knowledge and tools, and create the enabling conditions (including recognition and support networks) these champions need, to advance equitable WEFE nexus decision-making and implementation.